Estudos funcionais de uma possível cisteíno protease de Xanthomonas axonopodis pv. citri - Santos, Guilherme Rodrigo Reis Monteiro dos (Universidade Federal de São Carlos, 2007)
Cysteine proteases are enzymes found in many organisms and are characterized by the presence of cysteine residue in their active site. These proteases play an important role in the organism metabolism. In pathogenic organisms, for example, cysteine proteases may be involved in the pathogenicity process by unbalancing of the biological functions of the host (biochemical and physiological regulation). Since they are involved in several diseases, these enzymes have been considered of great interest for many researchers. The current work aims to express in E. coli a recombinant form of an ORF XAC2853 predicted to be a cysteine protease by annotation of the genome of Xanthomonas axonopodis pv citri. This bacterium is responsible for citrus canker, an infection affecting citrus species which can be evidenced by superficial lesions and early fall of leaves and fruits, thus resulting in significant losses to world agriculture. After expression, the protein was purified by nickel column affinity chromatography and inclusion body solubilization, inasmuch as this protein is almost fully insoluble. The purified protein was used to investigate the activity against such synthetic substrates as Z-FR-MCA and Z-RR-MCA, and no proteolytic activity was found. However, studies in vivo using clones of E. coli expressing the recombinant protein evidenced proteolytic activity against casein. In an attempt to demonstrate the involvement of this probable protease in the pathogenicity of Xac, the knockout of the cromossomal gene in Xac was performed. A mutant having the disrupted gene was obtained and characterized. The assays of the mutant growth, when compared with the wild strain, indicate that the cysteine protease may be involved in the pathogenicity of Xac, since the inactivation of its gene by the transposon insertion resulted in a less virulent strain. In this sense, this protein may be a promising target for the combat of citrus canker.
Keywords: Biologia molecular; Biotecnologia; Clonagem; Expressão gênica; Mutação cromossômica; Bactérias fitopatogênicas; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR